Analysis of the applicability of methods of underground construction of civil and industrial buildings - I. S. Dovolnov (Архитектура, строительство, транспорт)
The object of comparative analysis is the methods of underground construction.   The article describes the technologies of open, semi-closed, combined and closed methods of underground buildings’ construction. The authors consider various types of pit fixing, and methods of excavation, depending on the choice of construction method, and provide a comparative table based on the analysis of the applicability of these methods. The results indicate the advantages of the semi-closed method of underground construction in the civil and industrial buildings’ construction.